Perceived Quality of Life Among Adults With Hearing Loss: Relationships With Amplification Device and Financial Well-Being. (July 2019) - Michael, Rinat; Attias, Joseph; Raveh, Eyal
The current study explored the relationship between perceived quality of life and financial well-being among adult cochlear implant (CI) users as compared with hearing aid (HA) users. Participants were 66 adults: 30 CI users and 36 HA users. They completed the Perceived Quality of Life for Deaf and Hard-of-Hearing (DHH) scale, the In Charge Financial Distress/Financial Well-Being scale, and a background questionnaire. Significant differences were found between the two study groups in two perceived quality-of-life factors: participation, t (58) = 1.71, p < .05, and perceived stigma, t (58) = −1.80, p < .05. CI users reported higher levels of participation and lower levels of perceived stigma as compared with HA users. In addition, financial well-being was a significant predictor of participation (β = .32, p < .05), and CI users who used their device for a longer time reported higher levels of financial well-being ( r = .35, p < .05). Research findings emphasize the possible contribution that both CIs and financial well-being may have on the perceived quality of life of DHH adults. In addition, time since implantation may be an important variable when measuring improvements after cochlear implantation, especially when evaluating long-term processes, such as changes in financial well-being.